Biomarcadores comportamentais, histopatológicos e proteômicos da toxicidade aguda da formulação comercial do herbicida glifosato em poecilia reticulata - ROCHA, Thiago Lopes (2012)
The mechanism of acute toxicity of the commercial formulation glyphosate, Roundup Transorb® (RDT), was investigated in the guppy (Poecilia reticulata) gills using proteomic technologies associated with analyses of histopathological indexes (HI´s), followed by quantification of histopathological lesions of the gills. Additionally, the present study describes a protocol for the analysis of fish behavior using measurements of the Index of morphofunctional behavior (Imb) and Total (Itb). The results indicate that the acute toxicity of RDT may change P. reticulata behavior as a consequence of changes in the expression of proteins associated with cyto-histopathological lesions of the gills. RDT LC50,96h for guppy females was 7.54 ± 0.93 μL.L-1, indicating that the species is moderately sensitive to this herbicide. Acute exposure to RDT sublethal concentration of 3.8 μL.L-1 induced time-dependent histopathological lesions of the gills in different epithelial and muscle cell types. HI´s were related to increase in severity and frequency of histopathological lesions and suggest that RDT may cause regressive, circulatory, and progressive disorders in the guppy gills. Two-dimensional electrophoresis associated with mass spectrometry and biocomputing permitted to verify 48 spots of proteins/isoforms regulated by RDT, which are involved in different cell processes, such as energy metabolism, regulation and maintenance of cytoskeleton, metabolism of nucleic acids and proteins in response to stress. The study of behavior biomarkers (BM´s) indicates that Imb and Itb were viable in the analysis of P. reticulata behavioral changes induced by RDT. Furthermore, proteomic and histological changes in the gills of P. reticulata induced by RDT may be histopathological and proteomic BM´s to biomonitor water pollution caused by glyphosate-based herbicides.